Prenatal Drug Exposure and Adolescent Cortisol Reactivity: Association with Behavioral Concerns. Issue 7 (September 2016) - Buckingham-Howes, Stacy; Mazza, Dayna; Wang, Yan; Granger, Douglas A.; Black, Maureen M.
ABSTRACT: Objective: To examine stress reactivity in a sample of adolescents with prenatal drug exposure (PDE) by examining the consequences of PDE on stress-related adrenocortical reactivity, behavioral problems, and drug experimentation during adolescence. Methods: Participants (76 PDE, 61 non-drug exposed [NE]; 99% African-American; 50% male; mean age = 14.17 yr, SD = 1.17) provided a urine sample, completed a drug use questionnaire, and provided saliva samples (later assayed for cortisol) before and after a mild laboratory stress task. Caregivers completed the Behavior Assessment System for Children, Second Edition (BASC II) and reported their relationship to the adolescent. Results: The NE group was more likely to exhibit task-related cortisol reactivity compared to the PDE group. Overall behavior problems and drug experimentation were comparable across groups with no differences between PDE and NE groups. In unadjusted mediation analyses, cortisol reactivity mediated the association between PDE and BASC II aggression scores (95% bootstrap confidence interval [CI], 0.04–4.28), externalizing problems scores (95% bootstrap CI, 0.03–4.50), and drug experimentation (95% bootstrap CI, 0.001–0.54). The associations remain with the inclusion of gender as a covariate but not when age is included. Conclusion: Findings support and expand current research in cortisol reactivity and PDE by demonstrating that cortisol reactivity attenuates the association between PDE and behavioral problems (aggression) and drug experimentation. If replicated, PDE may have long-lasting effects on stress-sensitive physiological mechanisms associated with behavioral problems (aggression) and drug experimentation in adolescence.